Teaching training in ICT and digital competences in Higher Education System - Jorge Francisco Barragán López; Juan González Martínez; Teresa Guzmán Flores; Beatriz Zempoalteca Durán (Universidad de Guadalajara, 2017)
Currently, Information and Communications Technologies (ICT) have become essential tools in academic practice; however, its use within the teachinglearning process has focused only on digitizing educational acquis, while educational practice still preserves traditional, methods, instead of using collaborative environments and other benefits offered by the field of Web 2.0. Thus, this research, which corresponds to a quantitative-descriptive correlational level, it has been done through survey methodology. Its aim is to analyze the ICT training of teachers and students in relation to digital competence and the use of ICT in Web 1.0 and 2.0 in academic practice, in reference to some contextual factors in Higher Education System in administrative sciences in the metropolitan area of the city of Queretaro. It was found that there is a relation between of digital competence and teaching training in ICT, as well as a direct relation of the use of ICT among teachers and students. This affects academic performance, showing that the innovative use of ICT has favorable effect on student academic practice.